Physician Perspectives on the Implementation of a Trauma-Informed Care Initiative in the Maternity Care Setting - Huartson, Karolina; Hill, Todd; Killam, Teresa; Kelly, Martina; Racine, Nicole (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2022)
Objectives: To explore the barriers and facilitators from the perspective of family physicians on the implementation of a pilot trauma-informed care (TIC) initiative to promote resilience, with particular emphasis on asking about adverse childhood experiences (ACEs), in a maternity care clinic. Methods: Using an exploratory qualitative design, in-depth semi-structured interviews were conducted with family physicians who were practicing in a maternity clinic in a large Canadian city. Interviews were audio-recorded and transcribed verbatim. Transcripts were reviewed by three coders and themes were extracted using thematic analysis. Results: The analysis of 10 interviews yielded six thematic domains. Three domains pertained to perceived barriers to obtaining an ACEs history including: (1) concern about time management, (2) initial lack of physician comfort with TIC, and (3) cultural limitations of using the ACEs questionnaire. Three themes pertained to perceived facilitators of obtaining an ACEs history including: (1) the importance of a physician champion, (2) a supportive and flexible clinic environment, and (3) improved patient-physician relationships. Implications: In the context of a broader TIC initiative within a maternity care setting, asking patients about ACEs was generally perceived positively by physicians. Ensuring a supportive clinic environment and adequate staff training may be critical factors that contribute to successful implementation. Future research focused on diverse physician experiences in different settings are needed.